2020
DOI: 10.17161/jas.v6i1.7468
|View full text |Cite
|
Sign up to set email alerts
|

Does Leadership on the Field Get You Noticed Off It?: The Value of Varsity Sports to Corporate Recruiters

Abstract: An online correspondence study was conducted to explore whether professional recruiters screening candidates for entry-level corporate jobs would view leadership skills acquired through high level participation in amateur sports at the collegiate varsity level more favorably than those acquired through non-sports activities. The experimental manipulation randomly varied candidates’ athletic v. non-athletic leadership experience at university, their gender, and race. Eight hundred and twenty-eight corporate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These effects were largest in physically demanding occupations, although they were not driven by the physically demanding types of athletics. In another experiment, Tracy, Erkut, and Pappano (2020) found that college athletes were no more likely than non-athletes to receive an interview. In this study, however, the authors presented fictitious resumes to be evaluated by human resource professionals who knew they were participating in an academic survey, rather than job recruiters employed by a company truly seeking to hire an employee.…”
Section: Background and Prior Researchmentioning
confidence: 98%
“…These effects were largest in physically demanding occupations, although they were not driven by the physically demanding types of athletics. In another experiment, Tracy, Erkut, and Pappano (2020) found that college athletes were no more likely than non-athletes to receive an interview. In this study, however, the authors presented fictitious resumes to be evaluated by human resource professionals who knew they were participating in an academic survey, rather than job recruiters employed by a company truly seeking to hire an employee.…”
Section: Background and Prior Researchmentioning
confidence: 98%